RELIEF TANTRI DI PERTAPAAN GUNUNG KAWI BEBITRA DESA BITERA, GIANYAR - Sudiana, I Putu Yogi (Humanis; Volume 7. No. 1. April 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Relief of Tantri that is located in Pertapaan Gunung Kawi Bebitra. This area located at Bitera village, Gianyar Regency. This relief tells about friendship relation between Singa Pinggala and Lembu Nandaka. At the last this friendship relation is disturbed by Anjing Sembada. It is can be seen from character that is curved in forms of lion, ox and dog. This study obtained to know function and symbolic meaning from relief of Tantri at Pertapaan Gunung Kawi Bebitra. This research is qualitative research so that investigates this problem used some theories, they are : function theory and semiotics theory, meanwhile there are some techniques that is used to collect of data, they are : observation, interview, library research, After that used also some analysis, they are : qualitative analysis, symbol analysis, and comperative analysis. The result of study used to know that function of relief Tantri in Pertapaan Gunung Kawi Bebitra has two functions, they are : aesthetics function and religion function, and the meaning of simbolic about relief Tantri in Pertapaan Gunung Kawi Bebitra described about jealous, friendship, and angry. It can be seen from story and its relief panil. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Relief of Tantri, Pertapaan Gunung Kawi Bebitra, Function and symbolic meaning 1.